2013
DOI: 10.1016/j.mito.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol depletes mitochondrial DNA and inhibition of autophagy enhances resveratrol-induced caspase activation

Abstract: We recently demonstrated that resveratrol induces caspase-dependent apoptosis in multiple cancer cell types. Whether apoptosis is also regulated by other cell death mechanisms such as autophagy is not clearly defined. Here we show that inhibition of autophagy enhanced resveratrol-induced caspase activation and apoptosis. Resveratrol inhibited colony formation and cell proliferation in multiple cancer cell types. Resveratrol treatment induced accumulation of LC3-II, which is a key marker for autophagy. Pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…MtDNA damage and a subsequent accumulation of dysfunctional mitochondria can induce not only apoptosis but also autophagy, an adaptive, pro-survival response aimed at removing the damaged mitochondria. After 24 h incubation of human breast cancer MDA-MB-231 cells with resveratrol, a decrease in mtDNA content was observed when compared with control cells [78]. The decrease could result from autophagy, triggered in the cells in response to mtDNA damage caused by the treatment with resveratrol.…”
Section: Class VIII Mitocans: Mitochondrial Dna (Mtdna)-targeting Agentsmentioning
confidence: 93%
“…MtDNA damage and a subsequent accumulation of dysfunctional mitochondria can induce not only apoptosis but also autophagy, an adaptive, pro-survival response aimed at removing the damaged mitochondria. After 24 h incubation of human breast cancer MDA-MB-231 cells with resveratrol, a decrease in mtDNA content was observed when compared with control cells [78]. The decrease could result from autophagy, triggered in the cells in response to mtDNA damage caused by the treatment with resveratrol.…”
Section: Class VIII Mitocans: Mitochondrial Dna (Mtdna)-targeting Agentsmentioning
confidence: 93%
“…Lipophilic cations, such as the intercalating anticancer drug ditercalinium, causes selective mtDNA depletion by inhibiting DNA polymerase gamma activity in cultured mammalian cells, which could be more selective than ethidium bromide because it differentially accumulates in the mitochondria [70]. It has been shown that resveratrol depletes mtDNA during apoptosis induction in cancer cells [71]. Additionally, cisplatin shows preferential binding with mtDNA compared with genomic DNA, causing impairment of mitochondrial function and cell death [72].…”
Section: Potential Mitochondrial Targets For Cancer Therapymentioning
confidence: 99%
“…It is known that beclin 1 generates a pro-apoptotic protein fragment and also interacts with the anti-apoptotic Bcl-2 family protein to inhibit autophagy and initiate mitochondrial apoptosis (22). Prabhu et al (25) reported that the silencing of key regulators of autophagy, such as beclin 1 and autophagy protein (ATG)5, significantly enhanced Res-induced caspase activation. In the present study, western blotting results revealed that Res significantly increased the expression levels of Bax and decreased those of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%